The Study on Sorghum (Sorghum bicolor. L Moench) Soaking and Germination Time to Produce Low Tannin and Phytic Acid Flour - Narsih, Narsih; Yunianta, Yunianta; Harijono, Harijono (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Flour sorghum has not been exploited widely for food product such as other cereal flour because of the content of phytic acid and tannin in the seed. The modification of flour processing could reduce tannin and phytic content which could increase the flour quality. Time of soaking and seed germination have an important role for the production of high quality flour. The purpose of this research was to study the appropriate treatments of soaking time and seed germination to reduce tannin and phytic acid content.This study was carried out using factorial randomized block design with two factors, which were soaking time (24, 48 and 72 hours) and germination time (12, 24 and 36 hours). Data was analyzed by Anova and continued by Least Significant Difference or Duncan Multiple Range Test.The result showed that the soaking time of 72 hours and the germination time of 36 hours had the lowest tannin and phytic acid content which were 0.75% and 3.10 mg/g respectively. The low tannin and phyitic acid flour was applied on muffin bread.The sensory test of muffin hedonic scale score showed that the panelist stated like for color and slihtly like for texture.Keywords: sorghum, soaking, germination, tannin, phytic acid